Modulating the unfolded protein response with ONC201 to impact on radiation response in prostate cancer cells - Amoroso, Francesca (2022)
Funding Information: This work was supported by Movember Prostate Cancer UK Centre of Excellence (CEO13_2-004) to JOS and DJW and also by a grant from the Norwegian Research Council (230559) to IGM. IGM is also supported by the John Black Charitable Research Foundation. The authors acknowledge the Genomic Core Technology Unit, CCRCB, Queen’s University Belfast that performed the RNA-Seq Sequencing; the support of Fundação para a Ciência e Tecnologia (FCT-MCTES), Radiation Biology and Biophysics Doctoral Training Programme (RaBBiT, PD/00193/2012); and scholarships grants number SFRH/BD/114448/2016 to (FL). Publisher Copyright: © 2021, The Author(s).